Structural-phase state and mechanical properties of submicrocrystalline titanium alloy Ti-6Al-4V obtained with use of reversible hydrogen alloying; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Grabovetskaya G. P. Galina Petrovna (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа